Manufacturing of Form-molded Pulp Products (FMPPs) in the Papermaking Industry – A Review - Dariusz Danielewicz (BioResources)
The article reviews the history of the production of form-molded pulp products (FMPPs) and the current value of their production. The discussion includes fibrous intermediates and additional materials used to produce these products, the categories and properties of FMPPs, and principles of operation of machines used to produce them. It compares vacuum and overpressure molding techniques, and current and future trends in FMPPs production. FMPPs are produced from fibrous secondary and primary papermaking pulps, as well as other waste intermediates, the use of which can contribute to reducing the costs of producing these products. It was found that over the past dozen or so years, the state of knowledge on improving the strength properties of FMPPs and the use of biodegradable aids to improve their properties, including barrier properties, has significantly expanded. Drawing not yet published in review articles, showing devices for producing FMPPs using hydraulic molding and pressurized air molding methods are presented in a descriptive and comparative form used in the industry at the turn of the 1950s and 1960s. Possible future directions are considered for FMPPs developments in technology and further commercialization.